Unique and late onset infections after Dynamic Dynesys Stabilization in the lumbosacral spine - Po-Hsin Lin; Ting-Wei Chang; Zhuo-Hao Liu; Nan-Yu Chen; Jyi-Feng Chen (Medicine, 2026)
This study investigates a unique pattern of late-onset infections occurring exclusively in patients treated with the Dynamic Dynesys Stabilization (DDS) system for degenerative lumbosacral disease. Between 2013 and 2019, 571 patients underwent lumbosacral surgery using the DDS system. A total of 431 patients completed a minimum 2-year follow-up (mean: 5.3 years; range: 2.3–8.9 years). Data on late-onset infections (occurring > 6 months postoperatively) were analyzed, focusing on clinical presentations, comorbidities, radiological findings, and microbiological results. Nine patients (2.1%) developed late-onset infections at a mean interval of 32.5 months after the index surgery. Most affected patients (77.8%) had chronic comorbidities such as diabetes or chronic kidney disease. Common symptoms included low back pain (7/9, 77.8%), fever (3/9, 33.3%), and radiculopathy (2/9, 22.2%). Diagnosis was often delayed (mean: 7.3 weeks) due to indolent symptoms. Notably, screw loosening was observed in 100% of infected cases (9/9). Cultures frequently showed no growth (7/9), with Propionibacterium and Staphylococcus epidermidis identified in 2 cases. All patients recovered following implant removal and antibiotic therapy. Late-onset infection is an underrecognized complication of the DDS system, primarily affecting patients with chronic comorbidities. While the incidence was low, screw loosening was consistently observed in all infected cases. Although this finding requires validation in comparative studies, it may represent a potential clinical warning sign warranting further evaluation for deep peri-prosthetic infection. Prolonged clinical surveillance is recommended for this high-risk population.